2022
DOI: 10.1172/jci.insight.149870
|View full text |Cite
|
Sign up to set email alerts
|

ADAM8 signaling drives neutrophil migration and ARDS severity

Abstract: Acute respiratory distress syndrome (ARDS) results in catastrophic lung failure and has an urgent, unmet need for improved early recognition and therapeutic development. Neutrophil influx is a hallmark of ARDS and is associated with the release of tissue-destructive immune effectors, such as matrix metalloproteinases (MMPs) and membrane-anchored metalloproteinase disintegrins (ADAMs). Here, we observed using intravital microscopy that Adam8 –/– mice had impaired neutrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…had shown that an increase in C5a during sepsis inhibits neutrophil IL-8 secretion, resulting in neutrophil migration dysfunction through downstream signaling pathways mediated by C5aR and C5L2 ( 173 ). It is concluded that GPCR-mediated aggregation, activation, and apoptosis of the accumulated neutrophils in the lung of septic patients are important causes of ARDS and are related to the release of tissue-destructive immune mediators ( 174 , 175 ).…”
Section: The Contribution Of Neutrophils and Gpcrs In Sepsis-induced ...mentioning
confidence: 99%
“…had shown that an increase in C5a during sepsis inhibits neutrophil IL-8 secretion, resulting in neutrophil migration dysfunction through downstream signaling pathways mediated by C5aR and C5L2 ( 173 ). It is concluded that GPCR-mediated aggregation, activation, and apoptosis of the accumulated neutrophils in the lung of septic patients are important causes of ARDS and are related to the release of tissue-destructive immune mediators ( 174 , 175 ).…”
Section: The Contribution Of Neutrophils and Gpcrs In Sepsis-induced ...mentioning
confidence: 99%
“…The proliferation and differentiation of AECs may be indicated by the level of growth factors, such as hepatocyte growth factor (HGF) acting as a mitogen for AECs II, the increased level of which was associated with poor outcome for ALI patients [ 388 ] ( Table 3 ). Moreover, ECM regulators can be used as markers of the proliferative phase of ALI: high expression levels of genes, responsible for the ECM regulation (PTX3 [ 363 , 389 ], TIMP1 [ 364 ], TNC [ 365 ], MMP8 [ 366 ], PLAUR [ 390 ], ADAM8 [ 368 ]), are associated with increased severity and rapid progression of ALI with different etiologies, including COVID-19 ( Table 3 ).…”
Section: Prognostic Markers Of Acute Lung Injury and Pulmonary Fibrosismentioning
confidence: 99%
“…A disintegrin and metalloproteinase 8 Adam8 is an enzyme that participates in the recruitment of leukocytes from the pulmonary blood vessels into the lung tissue during acute lung inflammation [ 67 , 68 , 69 ]. Adam8 is not regulated by Timp1 or other Timps [ 70 , 71 ] such as matrix metalloproteinases and thus may a represent relatively independent way of regulating of inflammation.…”
Section: Resultsmentioning
confidence: 99%